Determinan Penggunanan Digital Banking Pada Generasi Y Dan Generasi Z Muslim Di Kota Banda Aceh - Muliza, Muliza (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
The development of information technology has given a new face to the financial and banking industry, such as the presence of digital banks. Implementation of Aceh Qanun Number 11 of 2018 concerning Sharia Financial Institutions (LKS) also does not become an obstacle for digital banking, because digital banks do not require physical services to carry out their activities. Currently, more than 90% of digital banks in Indonesia use conventional systems. The movement in the development of digital banks has shown quite significant growth in Indonesia, especially during the Covid-19 pandemic when demands for physical meetings were implemented. This research aims to look at the determinants of digital bank use among generations Y and Z Muslims in Banda Aceh City by analyzing the relationship between eight independent variables, namely economic value, ease of use, social influence, company reputation, promotion, features, curiosity and appreciation. The population in this research is all generations Y and Z Muslims in Banda Aceh City who have used digital banking services for at least 4 months. The sample used was 100 people using a purposive sampling technique. Data was collected by distributing questionnaires using a Likert scale instrument, which was then analyzed using multiple linear regression analysis techniques. The research results show that all variables except the sales promotion and curiosity variable have a significant effect on the intention to use digital banking in the city of Banda Aceh. Keywords : Digital Banking, Generation Y and Generation Z